PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KESEJAHTERAAN ANAK-ANAK PANTI - Herlina, Herlina; Safitri, Novi Ulfa; Susanti, Eva (Komunitas Manajemen Kompetitif, 2025)
Abstract: “Anugrah” orphanage is a social welfare institution that still depends on community assistance. Almost all of the operational costs of the orphanage come from individual or group or community assistance. Community empowerment can be mobilized as much as possible with social visit programs, funding and providing facilities to this orphanage. This community service (PkM) uses the Asset Based Community Development (ABCD) method which has a place-based framework that combines several principles. The implementation of PkM on Friday, March 21, 2025 was attended by 25 children of Anugrah orphanage, administrators and journalists. The children's enthusiasm in following the PkM implementation process can be seen from several questions asked which are curious about the practice of the world and the hereafter towards success. The continuity of material presentation and question and answer dialog is approximately 1.5 hours. Community empowerment in the form of social assistance is still very much needed by this orphanage. Empowerment, Community, Children, Orphanageroperty,